A method to identify and evaluate the legal and institutional framework for the management of water and land in Asia: the outcome of a study in Southeast Asia and the People?s Republic of China - Hannam, I. (International Water Management Institute, 2003)
By determining the capacity of relevant international, national and regional legislation to support sustainable use of water and land, planners, legislative drafters and policymakers have a basis for recommending legal and institutional reform. This report, based on an investigation into existing water- and land- management laws and issues in three countries in the region, offers a methodology that can be used for such evaluations.